The Influence of Audit Committee to Earnings Management - I Putu Sugiartha Sanjaya (Universitas Muhammadiyah Yogyakarta, Indonesia, 2006)
The role of the audit committee continues to be of importance to regulators. The New York Stock Exchange (NYSE) and the National Association of Securities Dealers (NASD) co-sponsored a Blue Ribbon Committee (BRC) to make recommendations for improving the effectiveness of the audit committee. In Indonesia, the Jakarta Stock Exchange (JSX) issued a regulation in 2001. The regulation emphasize all companies (which treaded publicly) must have audit committee. On the basis of the regulation, existing audit committee is expected to be able to restrict earnings management. According to Millstein (1999), it is totally consistent that good corporate governance practice points to the audit committee as the focal point for improvement in financial statements. This study investigates whether audit committee formation can reduce earnings management. Data is collected from JSX in 2001 and 2002 for manufacturing companies. Using independent sample t-test, the result suggests that audit committee can reduce earnings management.